Pembelajaran Videografi dan Fotografi di Desa Gisik Cemandi Sedati Sidoarjo - Faisal Reza Alfianza; Muhammad Zaenuri; Seration Neranain Jalu; Muhammad Rizqi Ariansyah; Angger Mahawira Agung Laksita; Salsabilla Prilia Nastiti; Athok Murtadhlo; Supriadi (LPPM Stikosa - AWS, 2024)
This research aims to improve the photography and videography skills of the Gisik Cemandi Village community, Sidoarjo Regency, as an effort to empower the economy and promote village potential through digital media. The activities were carried out in the framework of Field Work Lectures (KKL) by Stikosa-AWS students through a series of research-based programs, such as training in shooting, editing, and social media publication. The results showed an increase in community understanding and skills in utilizing technology for branding MSME products and promoting local marine tourism. With the active involvement of the community, this program also provides field work experience for students, while contributing to a sustainable empowerment model that can be applied in other villages.